Influence of Leadership and Digital Competence on Marketing Performance: Mediation by Innovation, Moderation by Competition - ., Marbawi; Faliza, Nur; Yahya, Aiyub; Malinda, Rina; Santika, Pipi (Journal of Ecohumanism, 2024)
This study investigates the influence of strategic leadership, digital proficiency, technological innovation, and the competitive landscape on marketing success, highlighting the mediating function of technological innovation and the moderating effect of the competitive environment. We collected data from 305 employees at Indonesian Sharia Bank, Aceh Sharia Bank, and PT Pupuk Iskandar Muda. The SEM-PLS analysis reveals that strategic leadership and digital competency significantly improve technical innovation and marketing performance. Technological innovation substantially enhances marketing outcomes. While the competitive landscape improves marketing performance, its moderating influence is significant and detrimental. The study highlights the need for developing leadership and digital skills to drive innovation. By investing in these fields and understanding the competitive landscape, companies can strengthen their competitive edge and improve marketing results. Persist in implementing these discoveries